Phosphorus and sulfur addition affects selenate and selenite availabilities in oxidic soils - Santos, Maria Jéssica Vieira dos (2018)
Selenium (Se) is an essential element for animals, including humans, acting to prevent various diseases, such as cancer. Because of the ever-increasing importance of adequate Se in human diets, it is fundamental to increase Se levels in agricultural products. In this context, several factors affect Se transfer from soils to plants, and as a result, to humans. Among these factors, competition for anionic sites (e.g., phosphate and sulfate) may influence this transference. With the aim of evaluating the adsorption of selenate (SeVI) and selenite (SeIV) and the effect of adding phosphorus (P) and sulfur (S) on the Se desorption, an experiment was carried out on oxidic soils with different physicochemical properties. Initially, different concentrations of Se (0, 1, 2, and 4 mg L -1 for SeVI and 0, 4, 8, and 16 mg L -1 for SeIV were added in the soils, as Na salts. Then, the desorption study was carried out by adding solutions containing P (0, 2.18, 4.36, 10.90, and 21.90 mg L -1 ) or S (0.75, 7.5, 15, and 30 mg L -1 ), added as monobasic sodium phosphate (NaH 2PO4 ) and sodium sulfate (Na 2SO4 ), respectively. Selenium adsorption varied as a function of Se speciation, Se doses, and soil texture, with SeIV being much more adsorbed than SeVI. In general, Se desorbed amounts increased upon increasing the concentrations of P and S added in solution. SeVI desorption was more affected by P and S in soils with high percentage of clay, while SeIV was released in greater quantity in the medium texture soil.